Laser surface engineering : processes and applications - Lawrence, J.; Waugh, D. G.; Aoyagi, N. (Woodhead Publishing, 2015)
Lasers can alter the surface composition and properties of materials in a highly controllable way, which makes them efficient and cost-effective tools for surface engineering. This book provides an overview of the different techniques, the laser-material interactions and the advantages and disadvantages for different applications. Part one looks at laser heat treatment, part two covers laser additive manufacturing such as laser-enhanced electroplating, and part three discusses laser micromachining, structuring and surface modification. Chemical and biological applications of laser surface engi.- Resumé vydavatel
Keywords: povrchy; lasery; surfaces; lasers; elektronické knihy; sborníky; electronic books; papers of several authors